Botanical Drugs in Traditional Chinese Medicine With Wound Healing Properties - Ning, Shuyi; Zang, Jie; Zhang, Bingyang; Feng, Xinchi; Qiu, Feng (Frontiers in Pharmacology, 2022)
Chronic and unhealed wound is a serious public problem which brings severe economy burdens and psychological pressure to patients. Various botanical drugs in traditional Chinese medicine have been used for the treatment of wounds since ancient time. Nowadays, multiple wound healing therapeutics derived from botanical drugs are commercially available worldwide. An increasing number of investigations have been conducted to elucidate the wound healing activities and the potential mechanisms of botanical drugs in recent years. The aim of this review is to summarize the botanical drugs in traditional Chinese medicine with wound healing properties and the underlying mechanisms of them, which can contribute to the research of wound healing and drug development. Taken together, five botanical drugs which have been developed into commercially available products, twenty-four botanical drugs with excellent wound healing activities and several multiherbal preparations were reviewed in this paper.